A character a day keeps the fruit on display: the influence of cartoon characters on preschoolers' preference for healthy food. (2015) - Baldassarre, Fabrizio; Campo, Raffaele
The objective of this research is to explore the role of cartoon characters in making fruit and vegetables more appealing to preschoolers: to this end, a sample of kindergarteners (5-6 years old) was involved, after having investigated their familiar food habits and their preferences about characters. Through a play-based methodology they were asked to select the tastiest food, choosing from fruit and vegetables, presented both with and without a sticker showing an image of their favourite characters, and branded salty and sweet snacks, presented in their traditional packaging without cartoon pictures. The findings show that characters deeply influenced children's choices in favour of healthy food, including in those children who were averse: cartoon characters can represent an incisive marketing tool to increase children's appreciation of fruit and vegetables.